Comparison Based Analysis of Advanced Tree Structures - *, Monika (IJRDO -Journal of Computer Science Engineering, 2015)
In this paper, the comparison is done among the most commonly used tree datastructures i.e. B-trees and binary trees. This comparison is made among all the variants of thesetrees on the basis of various operations done over them like creation, insertion, deletion, andsearching. The steps needed for these operations are counted and compared. This study canhelp us to find out easily that which tree data structure can be used in an application to make itefficient.